Memaksimalkan Potensi Bisnis Dengan Pengembangan Strategi Digital Marketing Yang Tepat (Universitas Gresik, 2023)
This article discusses the application of digital marketing after the Covid-19 pandemic, both for companies affected by the Covid-19 pandemic and those not affected by the pandemic. The Covid-19 pandemic has made the world change and many companies have had to adapt quickly to stay afloat. Digital marketing is considered to be an effective and appropriate solution to manage this problem. Digital marketing is the process of promoting products or services through digital media such as the internet, smartphones, and other technologies. The basic concept of digital marketing is to use technology to reach a wider audience and increase interaction with customers. This article describes some digital marketing methods that can be used by companies such as e-commerce, social media, email marketing, SEO, and online advertising. This article concludes that by implementing digital marketing, companies can increase visibility, increase website traffic, and increase sales as well as the obstacles that accompany it.